2019
DOI: 10.3389/fneur.2019.00887
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Neuromuscular Electrical Stimulation to Improve Gait in Cerebral Palsy: The Arc of Progress and Future Strategies

Abstract: Background: Neuromuscular deficits of children with spastic cerebral palsy (CP) limits mobility, due to muscle weakness, short muscle-tendon unit, spasticity, and impaired selective motor control. Surgical and pharmaceutical strategies have been partially effective but often cause further weakness. Neuromuscular electrical stimulation (NMES) is an evolving technology that can improve neuromuscular physiology, strength, and mobility. This review aims to identify gaps in knowledge to motivate future N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Neuromuscular or functional electrical stimulation (FES) is an example of the appropriate usage of temporal characteristics of sEMG recordings for determining the application of multichannel electrical stimuli to superficial skeletal muscles in order to control, compensate and/or correct their contractions (80)(81)(82)(83)(84)(85). In addition to a physiotherapy programme, it emphasizes task specificity, motor learning, and positive effects (86).…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…Neuromuscular or functional electrical stimulation (FES) is an example of the appropriate usage of temporal characteristics of sEMG recordings for determining the application of multichannel electrical stimuli to superficial skeletal muscles in order to control, compensate and/or correct their contractions (80)(81)(82)(83)(84)(85). In addition to a physiotherapy programme, it emphasizes task specificity, motor learning, and positive effects (86).…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…Targeting multiple joints with stimulation to multiple muscle groups has an additive effect on gait improvements [ 40 ] compared to varying results found in studies that target a single joint with stimulation to multiple muscle groups [ 31 , 41 , 42 ]. For example, stimulation of both rectus femoris and vastus lateralis were more effective in improving posture than stimulation of each muscle alone during walking in one child with CP [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were shown by Rose et al in three participants using a multi-channel FES system [ 45 ]. Although case studies have recently demonstrated the potential of improving gait when targeting multiple joints with multi-channel FES systems [ 44 , 45 ], evidence is limited [ 40 ]. Advancement in FES technology resulting in improved stimulation timing may contribute to differences between older and more recent multi-channel FES studies [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that incorporation of NMES with motorized assistance is integral to achieving optimal long-term outcomes for those with crouch gait. NMES has the unique capability to increase muscle strength and size [21], inhibit or reduce spasticity [22,23], and enhance motor performance during specific tasks through precisely timed muscle activation or sensory cues [24]. Furthermore, peripheral muscle stimulation may stimulate greater neuroplastic changes in sensorimotor brain regions during gait training [25].…”
Section: Introductionmentioning
confidence: 99%